Interdisciplinary Assessment of Hygiene Practices in Multiple Locations: Implications for COVID-19 Pandemic Preparedness in Vietnam - Nguyen, Trang Huyen Thi; Le, Huong Thi; Le, Xuan Thi Thanh; Do, Toan Thanh Thi; Ngo, Toan Van; Phan, Hai Thanh; Vu, Giang Thu; Nguyen, Tu Huu; Phung, Dung Tri; Nghiem, Son Hong; Vu, Thuc Minh Thi; Nguyen, Thu Ha; et al. (Frontiers in Public Health, 2021)
Due to the shared border with China, Vietnam faced risks from the COVID-19 pandemic at the early stages of the outbreak. Good hygiene practices were considered an effective prevention method, but there were only minimal data on the effectiveness of hygiene practices against the pandemic at the community level. Thus, this study aims to assess hygiene practices in society by using a community-based survey. A cross-sectional study using survey monkey was conducted from December 2019 to February 2020. The Snowball sampling technique was used to recruit participants and exploratory factor analysis was applied to scrutinize the construct validity of the measurement. We used the Tobit regression model to assess the association. Hygiene in a high-risk environment and hygiene in the social and educational environment were two main factors after applying the EFA method. Participants grade community sanitation quite low (around 6 out of 10). Furthermore, the mean score of hygiene practice at a local level in a high-risk environment was slightly low at 6.0. The score of sanitation in the Central region (5.3) was quite low compared to the North (5.8) and the South (6.2). The most high-risk environment was construction, industrial zone and food safety. Moreover, younger respondents were more likely to report poorer hygiene practices in high-risk environments (Coefficient = −1.67; 95% CI = −3.03; −0.32) and social and educational environment (Coefficient = −1.29; 95% CI = −2.54; −0.04). Our study gives an insight into pandemic preparedness at the grassroots level. The findings suggest the necessity of specific communication education for society to improve the compliance of hygiene practices to prevent the spreading of COVID-19.